Pluralism and Mysticism in the Thought of Paul K. Feyerabend - Coniglione, Francesco (Filozoficzne Aspekty Genezy, 2024)
Feyerabend’s positions regarding methodological pluralism and the consequent critique of the monism of Method proposed by the Popperian school are well known. Less analyzed is the significance of his scientific pluralism and the idea that a multiplicity of cognitive approaches to reality is possible, especially in relation to its “abundance” — the many ways in which it presents itself, its complexity, and the fact that consequently it can be approached and interpreted from different points of view. This aspect has led Feyerabend’s reflections to emphasize what is typically relegated to the realm of the irrational, and has enabled him to discover the extent of the unspoken and implicit aspects of scientific knowledge, thereby emphasizing the mystical dimension of humanity’s relationship with the world, which usually escapes rational analysis.